Accuracy of probing attachment levels using a new computerized cemento-enamel junction probe - R Deepa; Shobha Prakash (Wolters Kluwer Medknow Publications, 2012)
Background and Objectives: The assessment of clinical attachment level (CAL) represents the "gold standard" for diagnosing and monitoring periodontal disease. The aim of the present study was to evaluate the performance of the newly introduced cemento-enamel junction (CEJ) probe in detecting CAL, using CEJ as a fixed reference point, and to compare the CEJ probe with the Florida stent probe (FSP) as well as with a standard manual probe, University of North Carolina-15 (UNC-15). Materials and Methods: Three examiners recorded the probing attachment level in 384 sites in case group (chronic periodontitis), and in 176 sites, in control group (healthy periodontal status), using the three probes. Subjects included both the sexes and ranged from 35 to 45 years. The experimental design was structured to balance the intra- and inter-examiner consistency at the same site during the two visits. Results: CEJ probe showed higher intra-and inter-examiner consistency over both FSP and UNC-15 in both the case and control groups. Frequency distribution of differences of various magnitudes of repeated measurements ≤1 mm was in the higher range of 86.8% to 87.5% for CEJ probe. The FSP was more reproducible than UNC-15 in detecting relative attachment level (RAL). Interpretation and Conclusion: CEJ automated probe was found to have greatest potential for accuracy and consistency in detecting CAL than FSP and UNC-15. The automated probes appeared to be more reproducible than manual probes.